Association of Burnout and Depression symptoms and their prevalence among medical students in Karachi, Pakistan - Tafazzul Hyder Zaidi; Mubashir Zafar; Amber Ilyas; Momina Khan; Rafia Ghani; Rahat Naz; Ayesha Mubbashir (Russian Open Medical Journal)
Background — The mental health of medical students has long been a concern. Symptoms of depression and burnout are common among medical students, but the overlap of symptoms of both diseases with risk factors remains unclear. The goal of this study was to determine the prevalence of burnout and depression symptoms’ overlap in medical students. Methods — This cross-sectional study was conducted among students of the clinical course (3rd, 4th and 5th years). A multistage stratified random sampling design was used to select 284students that were offered a validated and structured questionnaire that included a modified Oldenburg Burnout Inventory and Patient Health Questionnaire-9 to assess their emotional burnout and depression, respectively. Chi-square and multinomial regression analyses were done to identify overlapping symptoms of burnout and depression with association of risk factors with dependent variable. Results — Out of 284 students, 13% had symptoms of severe depression, 24% had high burnout symptoms, and 32% had overlapping symptoms of burnout and depression. In regression analysis, higher academic year more than 2 times (5th year, OR 2.03, 95% CI 1.42-7.96, p-value 0.004) and living at dormitory more than 3 times (OR 3.97, 95% CI 1.97-5.01, p-value 0.003) were more likely associated with more extensive overlap of burnout and depression symptoms. Conclusion — There is a high prevalence of burnout and depression symptoms among medical students, with a strong association between the two disorders. Early burnout detection and psychiatric therapies given to affected students and these disorders management training at medical school, may help reduce negative consequences of these conditions.